Medpredmetno povezovanje in pouk jezikov (University of Maribor Press, 2024)
Cross-Curricular Integration and Language Teaching. The publication provides theoretical, applied and empirical insights into the various possibilities and opportunities for integrating non-language and language teaching, which we briefly refer to in the editorial as Learning for Life! The contributions are grouped into five themes addressing the following aspects: teachers’ views on language teaching, the implementation of cross-curricular integration at different points in the education vertical, cross-curricular integration as an opportunity for individual languages, language integration from the perspective of other fields, and comparisons and experiences of school systems with cross-curricular integration elsewhere. The contributions make an important contribution to the reflection of decision-makers, school policy-makers and actors in the learning process on much-needed change, on the relativisation of the boundaries between the sciences and on the importance of meaningful language learning and teaching that prepares students for life. The problems we solve are not confined to a single field or a single language, but are holistic and require an understanding of different perspectives on a particular problem, and require knowledge and understanding of different languages. Fächerübergreifende Integration und Sprachunterricht. Die Publikation bietet theoretische, angewandte und empirische Einblicke in die verschiedenen Möglichkeiten und Chancen der Integration von nicht-sprachlichem und sprachlichem Unterricht, die wir im Leitartikel kurz als Learning for Life! bezeichnen. Die Beiträge sind in fünf Themenbereiche gegliedert, die sich mit folgenden Aspekten befassen: die Ansichten der Lehrkräfte über den Sprachunterricht, die Umsetzung der fächerübergreifenden Integration an verschiedenen Stellen der Bildungskette, die fächerübergreifende Integration als Chance für einzelne Sprachen, die sprachliche Integration aus der Perspektive anderer Bereiche sowie Vergleiche und Erfahrungen von Schulsystemen mit fächerübergreifender Integration in anderen Ländern. Die Beiträge leisten einen wichtigen Beitrag zur Reflexion von Entscheidungsträgern, Schulpolitikern und Akteuren im Lernprozess über dringend notwendige Veränderungen, über die Relativierung der Grenzen zwischen den Wissenschaften und über die Bedeutung eines sinnvollen Sprachenlernens und -lehrens, das die Schüler auf das Leben vorbereitet. Die Probleme, die wir lösen, beschränken sich nicht auf ein einziges Fachgebiet oder eine einzige Sprache, sondern sind ganzheitlich und erfordern ein Verständnis für verschiedene Perspektiven auf ein bestimmtes Problem sowie die Kenntnis und das Verständnis verschiedener Sprachen.